Analytical Solutions for Girder Distribution Factor in Steel-Concrete Composite Girders with the Effect of Parapets - Zejun Zhang; Yongjian Liu; Bowen Feng; Yinping Ma; Guojing Zhang (Advances in Civil Engineering)
The existing studies have shown that parapets have great influence on the girder distribution factor (GDF) of bridges. However, there is no method in the design guide to estimate the GDF considering the effect of parapets. This research aims to develop a simplified method for estimating the GDF by considering the effect of parapets. First, a simply supported steel-concrete composite girder bridge was tested to investigate the effect of parapets on the GDF. Then, finite-element (FE) model was established and verified by the field test data of strain and deflection. In addition, error study showed that the bending stiffness of the bridge was increased by about 92% and 19.1%, respectively, due to the effects of parapet and continuous layer. As the effect of the continuous layer on each girder was relatively uniform, the simplified method was optimized only considering the effect of the parapet. Finally, the effect of the parapet on the GDF was compared and discussed. Considering the effect of the parapet, the GDF of the exterior girder calculated by the simplified method and FE analysis decreased by about 26.92% and 23.53%, respectively, and the adjacent interior girder decreased by about 15.22% and 12.77%, respectively. Comparing the GDF calculated by the AASHTO LRFD specifications, the GDF calculated by the simplified method decreased by about 30.77% in the exterior girder and 41.30% in the interior girder, respectively. The results indicate that the method of calculating the GDF without considering the effect of the parapet in AASHTO LRFD specifications is conservative. The GDF calculated by the simplified method was basically close to the field test results, meaning that the proposed simplified method considering the effect of the parapet was relatively accurate.